Newcastle disease virus hemagglutinin neuraminidase as a potential cancer targeting agent - Baradaran, Ali; Yusoff, Khatijah; Shafee, Norazizah; Abdul Rahim, Raha (Ivyspring International Publisher, 2016)
The hemagglutinin-neuraminidase (HN) protein of Newcastle disease virus (NDV) with its immunotherapeutic activities and sialic acid binding abilities is a promising cancer adjuvant. The HN was surfaced displayed on Lactococcus lactis and its cancer targeting ability was investigated via attachment to the MDA-MB231 breast cancers. To surface display the HN protein on the bacterial cell wall, HN was fused to N-acetylmuraminidase (AcmA) anchoring motif of L. lactis and expressed in Chinese hamster ovary cells. The expressed recombinant fusion proteins were purified and mixed with a culture of L. lactis and Lactobacillus plantarum. Immunofluorescence assay showed the binding of the recombinant HN-AcmA protein on the surface of the bacterial cells. The bacterial cells carrying the HN-AcmA protein interacted with the MDA-MB231 breast cancer cells. Direct and fluorescent microscopy confirmed that L. lactis and Lb. plantarum surface displaying the recombinant HN were attached to the breast cancer MDA-MB231 cells, providing evidence for the potential ability of HN in targeting to cancer cells.